Killer cell immunoglobulin-like receptor (KIR) genes and their HLA ligands in a Brazilian population - Daniela Maira Cardozo; Amanda Vansan Marangon; Fernando Guimarães; Silvia Marques; Sofia Lieber; Márcia Delamain; Francisco Aranha; Jeane Eliete Laguila Visentainer; Cármino Antonio de Souza (Innate Immunity, 2023)
Killer cell immunoglobulin-like receptors (KIR) exhibit extensive diversity, giving rise to different KIR profiles in populations worldwide. This study aimed to investigate the distribution of KIR genes and HLA ligands in a population from Campinas, southeastern Brazil (n  =  292), and to compare their results with other populations. A comprehensive analysis of population-specific genes, genotype, and haplotype frequencies of KIR may facilitate a better understanding of their evolution and role in immunity. The genotyping of 16 KIR genes and HLA class I alleles was performed by the reverse sequence-specific oligonucleotide methodology using the Luminex platform (One Lambda, Inc., Canoga Park, CA). The framework genes were present in all individuals, with the most common non-framework KIR genes detected being KIR2DP1(96.6%), KIR2DL1(95.5%), KIR3DL1(94.5%), KIR2DS4(93.8%) and KIR2DL3(87.3%). KIR2DS1, KIR2DS3, KIR2DS5, and KIR3DS1 presented frequencies below 40%. KIR2DL2, KIR2DL5, and KIR2DS2 showed intermediate frequencies (between53% and 58%). The activating gene KIR2DS5 was the least common in this population (30.8%). Forty-five KIR profiles were found with the commonest being the homozygous A haplotype (27.4%). The distribution of KIR genes in the Brazilian population is similar to Caucasian European and Euro-descendant populations.